A precarização da força de trabalho no serviço público de saúde: As condições e relações de trabalho dos Assistentes Sociais do NASF - Campos, Sayonara de Azevedo Gomes (2012)
Considering the current context of the labor force, this study discusses the precarious nature of the folding process, relationship and working condition of the social worker teams entered in the Support Center for Family Health of the municipalities of Joao Pessoa Paraiba, Campina Grande, Cabedelo, Conde, and Santa Mamanguape Rita. The construct of changes during the nineties in reality the management of the workforce in the public sector, with contrareforma the state apparatus, reflected a process of deregulation of the normative framework of their workers. In health this situation was as a result of the measures of decentralization of primary care services, streamlining the federal level by transferring powers and tasks prior to their states and districts. Thus, this logic penetrates the conformation of health work incorporating the changes in the world of work and the world economy that has driven the increasing precariousness of work in the health services. For this, we used the theoretical arguments capable of advancing our understanding of the problems identified with actually performing this research with the professionals. The analysis of the peculiarities surrounding the precarious work of Social Workers in Nucleus pointed to the importance in unraveling mechanisms fight for better working conditions and relationships that these professionals are subjected, in the current configuration of the NASF studied.